Exsheathment and midgut invasion of nocturnally subperiodic Brugia malayi microfilariae in a refractory vector, Aedes aegypti (Thailand strain) - Intakhan,N. (Springer Verlag, 2015)
© 2014, Springer-Verlag Berlin Heidelberg. Exsheathment and midgut invasion of nocturnally subperiodic Brugia malayi microfilariae were analyzed using light and scanning electron microscopy in a refractory vector, Aedes aegypti (Thailand strain). Results showed that exsheathed microfilariae represented only approximately 1 % of the total microfilaria midguts dissected at 5-min post-infected blood meal (PIBM). The percentage of exsheathed microfilariae found in midguts progressively increased to about 20, 60, 80, 90, and 100 % at 1-, 2–5-, 6–12-, 18–36-, and 48-h PIBM, respectively. Importantly, all the microfilariae penetrating the mosquito midguts were exsheathed. Midgut invasion by the exsheathed microfilariae was observed between 2- and 48-h PIBM. SEM analysis revealed sheathed microfilariae surrounded by small particles and maceration of the microfilarial sheath in the midguts, suggesting that the midguts of the refractory mosquitoes might have protein(s) and/or enzyme(s) and/or factor(s) that induce and/or accelerate exsheathment. The microfilariae penetrated the internal face of the peritrophic matrix (PM) by their anterior part and then the midgut epithelium, before entering the hemocoel suggesting that PM was not a barrier against the microfilariae migrating towards the midgut. Melanized microfilariae were discovered in the hemocoel examined at 96-h PIBM suggesting that the refractory mosquitoes used melanization reactions against this parasite. This study provided evidence that A. aegypti (Thailand strain) has refractory mechanisms against B. malayi in both midgut and hemocoel.